Alaotaby defection speech in his Designation - ولاء صادق محسن بيداء محمد حامد (College of Education for Women, 2019)
we conclude that Alaotaby in his Designation, with respect to defects in speech or speech pathology, he cited a number of terms function on speech defects in voice and accent like , Aphasia, Alokla, Alaay, Alramz, Alhasr, Alfadm,and Alaghop, and pointed to the sound stop as a result of an accident or a problem or the speech organ deny the will of the speech, which refers to the refrain defect in sound organic. He also marked the disorders individual sound caused by the bug of sample and disability among individual like Alokla, node and aphasia - which hinders communication as well as other factors such as irregular sound product and not reporting to be into the future toward the Aljamjamah and whispering, and it can be said that he pointed out flaws fluency about : Dysarthria, Burbl , Stuttering , Stammering , Al-lafef , Altartim , and Fluency disorders. Alaotaby was keen in mention the differences between defects in accent and voice, He distinguish between (Alghonnh) and (Alkhona) Making the last stronger than the first in which marred the sound in bluegill. He cited a number of terms on what is going on of impediments in the function of speech, caused by the impact of foreign language pronunciation in Arabic like Altamtama , Accent , Alratanah , and Alajmah. You know this group in terms of recent studies by the term (multi- language).It is worth noting that the phonology role in speech therapy or speech pathology like the change in the pronunciation of the (R) caused by an error in the adhesion of the tongue in the roof of the throat, and stuttering in language. We can fix like these defects or helping to repair, through continuous training on the proper use of the members of the speech.